A sketch of the successful missionary work of William Duncan amongst the Indian tribes in northern British Columbia, from 1858 to 1901 - Begg, Alexander, 1825-1905. (Victoria, B.C. : [s.n.], 1910)
Cover title. Mode of access: Internet.